PEDAGOGICAL ASPECTS OF EDUCATION FOR ELEMENTARY SCHOOL STUDENTS IN THE CONDITIONS OF INCLUSIVE EDUCATION (Analysis of International Sciences, 2024)
This article explores the pedagogical aspects of education for elementary school students in the context of inclusive education. Inclusive education emphasizes the inclusion of students with diverse abilities, backgrounds, and learning styles in regular classrooms. The article discusses various pedagogical strategies that can support inclusive practices, including peer modeling, sensory integration, collaborative goal setting, flexible assessments, and cultivating empathy and respect. It also highlights the importance of creating a supportive and inclusive classroom environment, involving parents and caregivers, and engaging in continuous professional development. Additionally, the article emphasizes the significance of universal design for learning, differentiated instruction, and the use of assistive technology to meet the individual needs of students. By implementing these pedagogical approaches, educators can create inclusive learning environments that foster academic achievement, social-emotional development, and a sense of belonging for all students.